Corporate Social Responsibility in the Indian Context - Dutta, P. K.; Chatterjee, Somnath (Prabandhan: Indian Journal of Management, 2010)
Till the dissolution of the Soviet Union, formally in 1989, in academic and popular discussions, the world used to be divided into three parts the First; Second; and Third worlds. From an economic structure point of view, the First world economies consisted of the market economies, with freedom for entrepreneurs domestically, and relatively free trade in exports and imports. The US, EU and Japan were the main constituents.The Second world was made up of centrally planned and administered economies, with state ownership of enterprises, and limited exports and imports; mainly through bilateral relations. Russia, the East European and Central Asian countries, were the main parts. The Third world consisted of all other countries, mostly in Asia, Africa and Latin America.